Karyotype diversity among predatory Reduviidae (Heteroptera) - Bardella, Vanessa Bellini [UNESP]; Gil-Santana, Hélcio Reinaldo; Panzera, Francisco; Vanzela, André Luís Laforga (Pensoft Publishers, 2014)
Species of infraorder Cimicomorpha of Heteroptera exhibit holokinetic chromosomes with inverted meiosis for sex chromosomes and high variation in chromosome number. The family Reduviidae, which belongs to this infraorder, is also recognized by high variability of heterochromatic bands and chromosome location of 18S rDNA loci. We studied here five species of Reduviidae (Harpactorinae) with predator habit, which are especially interesting because individuals are found solitary and dispersed in nature. These species showed striking variation in chromosome number (including sex chromosome systems), inter-chromosomal asymmetry, different number and chromosome location of 18S rDNA loci, dissimilar location and quantity of autosomal C-heterochromatin, and different types of repetitive DNA by fluorochrome banding, probably associated with occurrence of different chromosome rearrangements. Terminal chromosome location of C-heterochromatin seems to reinforce the model of equilocal dispersion of repetitive DNA families based in the bouquet configuration.
Keywords: 18S rDNA; Cimicomorpha; DAPI/CMA3 banding; Heteroptera; Holokinetic chromosomes